Possibilidades dialogais entre Byung Chul Han e Zygmunt Bauman - Carvalho, Cristiano Silva de (My University, 2023)
The aim of this Dissertation is to show the dialogue possibilities between Byung Chul Han and Zygmunt Bauman. The dialogues between these two thinkers were divided into three parts. The first is the relationship of the world of consumption, of contemporaneity with love, pain, beauty, sexuality, beauty, body, culture and the influence of the society of transparency. The second part focuses on violence that, according to Chul Han (2017), is divided into negative and positive. The human produces, with the society of performance, its own self-punishment. Bauman (2011) writes about postmodern violence that is on the streets and strengthened in the domestic environment. And the third dialogue possibility is about freedom, politics and ethics. Chul Han (2020) creates concepts of Foucault-inspired psychopolitics and infocracy in which democracy is being enveloped by the tsunami of data and information provided spontaneously by people. With the analysis of these two authors, perspectives are opened for Contemporary Philosophy to analyze the world of today and its circumstances, with the ability to question the concrete world and the current way of living. [resumo fornecido pelo autor]
O objetivo desta Dissertação é mostrar as possibilidades dialogais entre Byung Chul Han e Zygmunt Bauman. A proposta dessa produção textual é de articular e buscar concatenações das ideias desses dois pensadores. A primeira é sobre a relação do mundo do consumo, da contemporaneidade com o amor, a dor, a beleza, a sexualidade, o belo, o corpo, a cultura e a influência da sociedade da transparência. A segunda parte é foca na violência que, segundo Chul Han (2017), se divide em negativa e positiva. O humano produz, com a sociedade do desempenho, a sua própria autopunição. Bauman (2011) escreve sobre a violência pós-moderna que está nas ruas e se fortalece no ambiente doméstico. E a terceira possibilidade dialogal é sobre a liberdade, a política e a ética. Chul Han (2020) cria conceitos de psicopolítica inspirado em Foucault e infocracia no qual a democracia está sendo envolvida pelo tsunami de dados e informações fornecidas espontaneamente pelas pessoas. Com a análise desses dois autores, abrem-se perspectivas para a Filosofia Contemporânea analisar o mundo de hoje e suas circunstâncias, com a capacidade de questionar o mundo concreto e o modo de viver atual. [resumo fornecido pelo autor]
Keywords: Filosofia; Han, Byung-Chul, 1959-; Bauman, Zygmunt, 1925-2017; Análise do discurso; Philosophy; Discourse analysis